Conrad, the Textbook Writer - Finkel, Alvin (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
Marg Conrad, through her pioneering work on History of the Canadian Peoples, insured that feminist perspectives on Canadian history were integrated into the foundational materials that students receive in first-year Canadian survey history courses. She made clear to students the need to understand the gendered nature of social and political developments throughout Canada's history.